2017
DOI: 10.2175/106143017x14839994523424
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Production for Biodiesel from Sludge and Crude Glycerol

Abstract: Oleaginous yeast Trichosporon oleaginosus was studied for lipid production using municipal sludge with or without fortification of crude glycerol in a 15-L fermenter. The maximum lipid content (concentration) was 32.0% w/w (9.35 g/L), 33.6% (10.13 g/L), 33.3% (9.13 g/L), and 33.1% (9.03 g/L) w/w with the addition of 25, 50, 100, and 150 g/L glycerol, respectively. Glycerol concentration had little effect on lipid accumulation. However, glycerol concentration substantially affected increase of biomass concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Due to the increasing global population, the wastewater treatment sector is facing a monotonously increasing problem of an unmanageable volume of wastewater sludge for disposal. Different researchers have developed many different processes to valorize the nutritional components present in wastewater sludge to produce bioplastics, biodiesel, a biopesticide, and extra polysaccharides [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the increasing global population, the wastewater treatment sector is facing a monotonously increasing problem of an unmanageable volume of wastewater sludge for disposal. Different researchers have developed many different processes to valorize the nutritional components present in wastewater sludge to produce bioplastics, biodiesel, a biopesticide, and extra polysaccharides [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…While biodiesel provides a green alternative to current existing petrochemical fuel resources, due to the expansion of the biodiesel industry, an increasing amount of crude glycerol, a waste product of the biodiesel industry, is also generated [1,8]. Researchers have also tried to valorize the crude glycerol generated by biodiesel industry to produce other value-added products [3,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy balance was calculated based on the mass balance study. In the energy balance study, assumptions were made: (1) the biodiesel production from crude glycerol took place in the biodiesel production industry (where crude glycerol was generated), which suggested that there was no energy input from the transportation of crude glycerol; (2) the energy input from the utilization of crude glycerol was zero and the crude glycerol generated in esterification and transesterification was also zero; (3) methanol and H 2 SO 4 were not recovered after esterification and remained in crude glycerol; (4) the fermentation of T. oleaginosus for lipid production was conducted under aseptic condition, the power consumption was adopted from our previous study (Zhang et al, 2017); (5) the energy input in biomass harvesting, lipid extraction and transesterification was similarly estimated as utilized in our previous study (Zhang et al, 2017); (6) in the trans-esterification of lipid to biodiesel, methanol and NaOH were not recovered after the reaction; (7) the cell debris was assumed to be used as animal feed (Zhang et al, 2016).…”
Section: Mass and Energy Balance Of The Proposed Processmentioning
confidence: 99%